"Evaluating The Antibacterial Efficacy of Avocado Seeds Extract Against Enterococcus Faecalis: An In Vitro Study for Root Canal Irrigation" - Pal, Om Prasad; H B, Swetha; Dhamodaran, Thokala; M.G, Kavana; A S, Aathees; Johnson, Sandhra (Journal of Neonatal Surgery, 2025)
Root canal infections often involve Enterococcus faecalis, a resilient bacterium that can hide within tooth tubules. Traditional root canal irrigants have limitations, prompting research into alternative agents. One such candidate is an ethanol extract from avocado seeds, known for their bioactive compounds. If effective, avocado seed extract could offer a natural solution for combating Enterococcus faecalis during endodontic treatments, benefiting both patients and clinicians seeking improved strategies for root canal therapy..